The Relationship Between Self-Regulated Learning and Technology Literacy With Conceptual Understanding of Salt Hydrolysis - Fauzizah, Ulfa; Nurhayati, Nanik Dwi; Masykuri, Mohammad (J-PEK (Jurnal Pembelajaran Kimia), 2022)
The problems faced with learning chemistry at SMA Negeri Gondangrejo are students' low self-regulated learning and technology literacy, along with the student's lack of conceptual understanding. This research aimed to determine whether there is a relationship between self-regulated learning and technology literacy toward the conceptual understanding of salt hydrolysis subject matter. The research subject was 60 students of the 11th IPA SMA Negeri Gondangrejo. The research method used was a quantitive descriptive method with a correlational approach. The instrument used was a self-regulated learning and technology literacy questionnaire, also a two-tier multiple-choice question. The result of this research showed: 1) there was a positive relationship between self-regulated learning toward conceptual understanding, 2) there was a positive relationship between technology literacy to conceptual understanding, and 3) there was a positive relationship between self-regulated learning and technology literacy towards conceptual understanding.